Physicochemical property changes during oxidation process for diesel PM sampled at different tailpipe positions. (1st May 2018) - Gao, Jianbing; Tian, Guohong; Ma, Chaochen; Chen, Junyan; Huang, Liyong
Highlights: Sampling positions presented small effect on PM burn out temperature. PM oxidation activity dropped greatly after partial oxidation. Diesel PM shows orderly arranged crystallites and void cores after partial oxidation. Oxygen content decrease during oxidation process dominated oxidation activity drop. Abstract: Diesel particulate matter (PM) samples were collected at different tailpipe positions where sampling temperature differed greatly. All the samples were pre-heated in air at high temperature until 40% mass was burnt out. Physicochemical properties of diesel PM both before and after partial oxidation were analyzed, and to further figure out the reasons of oxidation activity changes in the oxidation process. The results showed that ignition temperature of PM whose sampling temperature was higher than 208 °C differed greatly from PM sampled below that temperature. After partial oxidation, sample 3 presented the hugest oxidation activity decreasing with burn out temperature increasing by 14.7 °C. Primary particle size distribution shifted to smaller diameter direction after partial oxidation, and particle stacking degree decreased evidently. Nanostructures of diesel PM transferred from onion like structures with randomly arranged crystallite to core-shell like structures with void inner cores. Oxygen-containing functional groups (carbonyl and hydroxy) decreased evidently after PM partial oxidation that was obtained from Fourier transform infrared spectroscopy (FTIR) spectra, it was consistent with the results of Raman parameter ID3 / IG .